Effect of pore throats on the reservoir quality of tight sandstone: A case study of the Yanchang Formation in the Zhidan area, Ordos Basin - Wei Fanrong; Yan Xinzhi; Bai Yubin; Bai Yanjun; Zhou Kai (Open Geosciences)
Due to the tight sandstone widespread development of nanoscale pore-throat systems, the microscopic pore-throat characteristics of tight reservoirs are the focus of research. Taking the main tight oil production province of the Ordos Basin in China as a case study, nuclear magnetic resonance (NMR), pressure-controlled mercury injection (PMI), scanning electron microscopy, and micro-computed tomography (μCT) are used to analyze the characteristics of four types of tight sandstones with different pore throats. Furthermore, the effects of pore throats on movable fluid, connectivity, and reservoir physical properties are analyzed. The results show that the pore throats of the four types of tight sandstones are obviously different, but they are all dominated by nanoscale pore-throat systems. From types I to IV, the pore types of the tight sandstone change from residual intergranular pores to the coexistence of feldspar dissolved pores and residual intergranular pores and then to the coexistence of residual intergranular pores and intergranular micropores. The T 2 NMR spectrum changes from a double peak to a single peak, the pore-throat connectivity revealed by μCT decreases from 83.8% for type I to 13.1% for type IV, the pore-throat volume ratio revealed by PMI decreases from 2.09 to 0.43, and the NMR movable fluid saturation decreases from 38.91 to 12.39%. Tight sandstone with larger pores and a uniform distribution has high movable fluid saturation and good pore-throat connectivity. Although the tight sandstone with dissolved pores and intergranular pores may have a medium porosity, the pore–throat connectivity deteriorates compared with high porosity sandstone. Large pore throats, which account for less than 15% of all pore throats, contribute more than 90% of the permeability, while pore throats less than 0.8 μm in diameter are major contributors to the reservoir space, and both the porosity and permeability decrease as the pore-throat diameter decreases.